Wirtschaft hacken Von einem ganz normalen Unternehmer, der fast alles anders macht - Lübbermann, Uwe (Büchner-Verlag, 2021)
What if you could do business in a completely different way? For entrepreneur Uwe Lübbermann 20 years ago, this question turned into what has become an ongoing social and economic experiment with his »Getränke & More«-collective Premium: Discounts for those who only buy small quantities; equal pay for all; freely available recipes; no written contracts and decision-making in the framework of a consensus-democratic structure. In order to counter the anti-social dynamics of the capitalist system with its own values, Premium has not only built up a crisis-proof, socially oriented company. Rather, it has itself become a persistent engine of change - a software that transforms the people, companies and systems it collaborates with by starting its own ›business-as-usual‹. Its commitment to social and environmental issues doesn't just influence business decisions, processes and ways of communicating - it spills over and transforms everyone who works with Lübbermann. For the first time, ›Wirtschaft hacken‹ describes the transformatory force of this approach -from the inside and the outside, in a biased yet critical way, in order to inspire and to be replicated. Accompanied by illustrations from Lennart Herberhold. Contributions by Claudia Brözel, Laura Marie Edinger-Schons, Martin Parker, Jürgen Radel and Anke Turner.